Prioritising the cardiac surgery waiting list: the angina patient's perspective. Issue 4 (April 1997) - Kee, F.; McDonald, P.; Gaffney, B.
Abstract : OBJECTIVE: To determine patients' views on how clinical and demographic factors should affect priorities for cardiac revascularisation. DESIGN: A descriptive survey of patients' views conducted immediately after angiography and treatment counselling. SUBJECTS: 136 patients who were awaiting coronary angioplasty in either of the two regional cardiology centres in Northern Ireland. RESULTS: About half the subjects (52%) felt that certain social factors such as having dependent relatives should be taken into account when deciding priority for surgery. A sizeable minority felt that younger subjects and non-smokers (40% and 44%, respectively) should be accorded higher priority, with older subjects and smokers being more likely to hold such views. CONCLUSIONS: While there is little evidence that demographic and lifestyle factors affect the relative efficacy of surgery, the challenge remains to devise a prioritisation guideline that can properly reflect societal values and the evidence base.